Analysis of reconfigurable assembly system framing systems in automotive industry - Zain, M.Z.M. (EDP Sciences, 2016)
Current trend in automotive industry shows increasing demand for multiple models with lean production. Prior to that, automotive manufacturing systems evolved from mass production to flexible automation. Material handling systems and equipment in a single assembly line with multiple models require high investment but with low throughput thus making production cost relatively high. Current assembly process of side structure and undercarriage with downtime occurrence during assembly process affecting production performance (quality, cost and delivery). Manufacturing facilities should allow more flexibility and increase intelligence evolving toward novel reconfigurable assembly systems (RAS). RAS is envisaged capable of increasing factor flexibility and responsiveness by incorporating assembly jig, robot and framing, which could be next generation of world class automotive assembly systems. This project research proposes a new methodology of framework reconfigurable assembly systems principles in automotive framing systems i.e. enhance assembly process between side structure assembly and undercarriage assembly which a new RAS is capable to reconfigure the assembly processes of multiple model on a single assembly line. Simulation software (Witness) will be used to simulate and validate current and proposed assembly process. RAS is expected to be a solution for rapid change in structure and for a responsively adjustable production capacity. Quality, cost and delivery are production key parameters that can be achieved by implementing RAS. Â© The Authors, published by EDP Sciences, 2017.